AMANAT DALAM GEGURITAN DARMA KUSUMA - Anggun Sri Pujangga, Desak Made (Humanis, 2016)
This study discusses the traditional Balinese literature shaped geguritan with the title "Darma Kusuma Geguritan". In geguritan there are eleven types of stanzas in 227 stanzas. The purpose of this study is to determine the mandate contained in the geguritan. This study has two objectives, namely general purpose and special purpose. The general objective of this research is to help the development of literature, and to clear the information or as a vehicle for the interests of fostering and developing the cultural treasure of the existence of literature shaped geguritan. Another common objective is to disseminate the results of research literature in particular geguritan GDK. The specific objective of this study was to describe the mandate contained in GDK. The method used in this stage is providing data reading methods, the data analysis phase of qualitative methods, and the stage presentation of the results of the data analysis, formal and informal methods. To support the method used recording techniques. The results achieved in this study, is the author of the message to be conveyed is the message of loyalty, ethics, good manners, good leadership and a message about the magical.
Keywords: Geguritan, mandate, Darma Kusuma